Microbial behavior and characteristics of biomass during starvation and their influence on ultrafiltration of activated sludge. Issue 16 (2nd April 2016) - Lee, W.; Son, Y.; Ahn, Y.; Kim, H.; Kim, S.; Kang, S.; Lee, C.
Abstract: Biological and physico-chemical properties of biomass under different growth phases are essential to characterize membrane fouling in membrane bioreactors (MBRs). This study assessed microbial behavior and characteristics under stationary and death phases as starvation progressed and their influences on membrane fouling during ultrafiltration of biomass in MBRs. As starvation progressed, samples were periodically drawn to be measured for biological and physico-chemical properties of the biomass, and for ultrafiltration (30, 000 Daltons) tests. Ultrafiltration experiments exhibited fouling resistances caused by biomass and supernatant increased as starvation progressed, and the death phase of microbial growth exhibited more potential in membrane fouling than the stationary phase. Particulates were more responsible for ultrafiltration membrane fouling in the stationary phase of microbial growth, but soluble materials were more accountable in the death phase of microbial growth. Statistical analysis indicated biomass with lower activity could experience higher fouling potential during ultrafiltration of biomass.